Congenital depressed fracture of the skull in a neonate - Atay, Enver; Tokmak, Mehmet; Can, E.; Ovalı, Hüsnü Fahri (My University, 2012)
Objective: Congenital depression of the skull is a rare event and the cause is not always clear. It may be complicated by brain injury, hematoma and epilepsy. This case is presented to draw attention to this rare congenital disorder which may raise suspicions in the family and discuss treatment options. Description: This baby boy was born at term by cesarean section and the depressed fracture of the right parietal bone, 5 cm × 4 cm, with a depth of 7.7 mm was noted at the first examination. Conventional and 3-dimentional computed tomography of the skull confirmed the diagnosis. The neurological examination was unremarkable. The depressed portion was elevated by surgery; the baby was growing well in the first month. Comments: Skull fracture is frequently assumed to have resulted from trauma, but it may occur prenatally.
Keywords: Depressed Fracture; Newborn; Skull Fracture